Unfolding physics from the algebraic classification of spinor fields - Hoff da Silva, J. M. [UNESP]; da Rocha, Roldão (Elsevier, 2013)
After reviewing the Lounesto spinor field classification, according to the bilinear covariants associated to a spinor field, we call attention and unravel some prominent features involving unexpected properties about spinor fields under such classification. In particular, we pithily focus on the new aspects - as well as current concrete possibilities. They mainly arise when we deal with some non-standard spinor fields concerning, in particular, their applications in physics. © 2012 Elsevier B.V.